2010
DOI: 10.1186/1743-422x-7-47
|View full text |Cite
|
Sign up to set email alerts
|

The cross-reactivity of the enterovirus 71 to human brain tissue and identification of the cross-reactivity related fragments

Abstract: BackgroundEV71 occasionally cause a series of severe neurological symptoms, including aseptic meningitis, encephalitis, and poliomyelitis-like paralysis. However, the neurological destruction mechanism was remained to be clarified. This study described the cross reaction between EV71 induced IgG and human brain tissue.ResultsCross reaction of the IgG from 30 EV71 infected patients' sera to human tissues of cerebra was observed, which suggested that some EV71 antigens could induce IgG cross-reactivity to human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 47 publications
2
18
0
Order By: Relevance
“…Four strong cross-reactivity inducing peptides between EV71 and human brain tissue were identified and two of them locate at VP2 and VP1, which may be responsible for the pathogenesis post infection [42], [47]. Several linear T-cell and B-cell epitopes of EV71 have been identified by different groups [9], [48].…”
Section: Discussionmentioning
confidence: 99%
“…Four strong cross-reactivity inducing peptides between EV71 and human brain tissue were identified and two of them locate at VP2 and VP1, which may be responsible for the pathogenesis post infection [42], [47]. Several linear T-cell and B-cell epitopes of EV71 have been identified by different groups [9], [48].…”
Section: Discussionmentioning
confidence: 99%
“…Human rhabdomyosarcoma cells (RD) for viral propagation were maintained in Dulbecco’s Modified Eagle Medium (DMEM) containing 10% fetal bovine serum (FBS), as previously described [37]. Four C4 EV71 strains were isolated from patients in China in 2008 by two passages, with the clinical specimens purified in RD cells (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…EV71 was initially isolated from the brain of a patient in California in 1969 (2), and it was found to trigger cytopathic effect and cellular apoptosis after infecting microvascular endothelial cells, Jurkat T cells and neuronal cells (3)(4)(5). EV71 was one of the major causes of a hand-foot-and-mouth disease (HFMD) epidemic associated with neurological sequelae (6)(7)(8)(9). Previously, Du et al reported that EV71 induced SH-SY5Y human neuroblastoma cells apoptosis by stimulation of endogenous microRNA let-7b expression (10).…”
Section: Introductionmentioning
confidence: 99%